Comparative effects of valsartan plus cilnidipine or hydrochlorothiazide on nocturnal home blood pressure. Issue 3 (26th January 2021) - Fujiwara, Takeshi; Hoshide, Satoshi; Tomitani, Naoko; Kanegae, Hiroshi; Kario, Kazuomi
Abstract: We tested our hypothesis that, in hypertensive patients with higher nocturnal home systolic blood pressure (HSBP) at baseline, a valsartan/cilnidipine (80/10 mg) combination would reduce nocturnal HSBP more markedly than a valsartan/hydrochlorothiazide (80/12.5 mg) combination. Patients measured their nocturnal HSBP over three nights prior to study randomization and at the end of treatment. Sixty‐three and 66 patients comprised the valsartan/cilnidipine and valsartan/hydrochlorothiazide groups; their respective baseline nocturnal HSBP values were 124.3 ± 15.6 and 125.8 ± 15.2 mm Hg ( P = .597). Nocturnal HSBPs were significantly reduced from baseline in both groups. Although the valsartan/hydrochlorothiazide group exhibited a significantly greater reduction in nocturnal HSBP compared to the valsartan/cilnidipine group (−5.0 vs. −10.0 mm Hg, P = .035), interaction between the treatment groups and the baseline nocturnal HSBP levels for the changes in nocturnal HSBP after the treatment periods was significant ( P = .047). The BP‐lowering effect of valsartan/cilnidipine was more dependent on baseline nocturnal HSBP than that of valsartan/hydrochlorothiazide.